Lipoprotein-associated phospholipase A2 activity, genetics and calcific aortic valve stenosis in humans. Issue 18 (7th July 2020) - Perrot, Nicolas; Thériault, Sébastien; Rigade, Sidwell; Chen, Hao Yu; Dina, Christian; Martinsson, Andreas; Boekholdt, S Matthijs; Capoulade, Romain; Le Tourneau, Thierry; Messika-Zeitoun, David; Engert, James C; Wareham, Nicholas J; et al.
Abstract : Background: Lipoprotein-associated phospholipase A2 (Lp-PLA2) activity has been shown to predict calcific aortic valve stenosis (CAVS) outcomes. Our objective was to test the association between plasma Lp-PLA2 activity and genetically elevated Lp-PLA2 mass/activity with CAVS in humans. Methods and results: Lp-PLA2 activity was measured in 890 patients undergoing cardiac surgery, including 476 patients undergoing aortic valve replacement for CAVS and 414 control patients undergoing coronary artery bypass grafting. After multivariable adjustment, Lp-PLA2 activity was positively associated with the presence of CAVS (OR=1.21 (95% CI 1.04 to 1.41) per SD increment). We selected four single nucleotide polymorphisms (SNPs) at the PLA2G7 locus associated with either Lp-PLA2 mass or activity (rs7756935, rs1421368, rs1805017 and rs4498351). Genetic association studies were performed in eight cohorts: Quebec-CAVS (1009 cases/1017 controls), UK Biobank (1350 cases/349 043 controls), European Prospective Investigation into Cancer and Nutrition-Norfolk (504 cases/20 307 controls), Genetic Epidemiology Research on Aging (3469 cases/51 723 controls), Malmö Diet and Cancer Study (682 cases/5963 controls) and three French cohorts (3123 cases/6532 controls), totalling 10 137 CAVS cases and 434 585 controls. A fixed-effect meta-analysis using the inverse-variance weighted method revealed that none of the four SNPs was associated with CAVS (OR=0.99 (95% CI 0.96 to 1.02, p=0.55) for rs7756935, 0.97 (95% CI 0.93 to 1.01, p=0.11) for rs1421368, 1.00 (95% CI 1.00 to 1.01, p=0.29) for rs1805017, and 1.00 (95% CI 0.97 to 1.04, p=0.87) for rs4498351). Conclusions: Higher Lp-PLA2 activity is significantly associated with the presence of CAVS and might represent a biomarker of CAVS in patients with heart disease. Results of our genetic association study suggest that Lp-PLA2 is however unlikely to represent a causal risk factor or therapeutic target for CAVS.